What good is grand strategy? power and purpose in American statecraft from Harry S. Truman to George W. Bush - Brands, Hal. (Ithaca Cornell University Press, 2014)
Grand strategy is one of the most widely used and abused concepts in the foreign policy lexicon. In this important book, Hal Brands explains why grand strategy is a concept that is so alluring―and so elusive―to those who make American statecraft. He explores what grand strategy is, why it is so essential, and why it is so hard to get right amid the turbulence of global affairs and the chaos of domestic politics. At a time when ?grand strategy? is very much in vogue, Brands critically appraises just how feasible that endeavor really is.
Includes bibliographical references (pages 207-259) and index.
Keywords: United States--Foreign relations--20th century